Relationship between learning agility and innovative work behavior among undergraduate student of University of Indonesia - Pitaloka, Yolla Chintya; Etikariena, Arum (Institute for Advanced Science Social, and Sustainable Future, 2024)
Background: Previous research has shown that university graduates in Indonesia face significant skill gap and behind from any country, spesifically among ASEAN countries, in term of innovation ability. Innovative ability can be developed for university students with the right variables. Thus, it might help student to focus on their self-development. Method: Quantitative and correlational research conducted to know how learning agility might related to innovative work behavior. Innovative Work Behavioral Scale developed by Janssen (2000) and Learning Agility Assessment Scale, developed and published by Gravett and Caldwell (2016), were used in study. Both scales were adapted and translated so they would fit with the undergraduates’ context. Result: In result, 539 of minimum Second year/3rd semester University Indonesia students were chosen. The statistics analysis technique used for hypothesis testing was Pearson’s Correlation. The result showed that learning agility is positively correlated with the innovative work behavior, r(537) = 0,61, p < 0,001. Conclusion: After this study, the result might be used as one of the references for university to develop program where student could develop their learning agility and become more innovative. Novelty/Originality of this study: This study reveals a significant relationship between learning agility and innovative work behaviour among Indonesian students, providing new insights into developing innovation capabilities at the higher education level. The findings offer an empirical basis for universities to design programs that enhance graduate competitiveness in the ASEAN context.